Evaluasi Sifat Morfologi dan Keanekaragaman Plasma Nutfah Sukun di Pulau Yamdena - Kamamas, Yulia; Jambormias, Edizon; Hehanussa, Meitty L (JURNAL BUDIDAYA PERTANIAN, 2025)
Breadfruit is one of the types of fruit-producing plants on Yamdena Island, with high nutritional content and important carbohydrates for body health in improving food security, and it is abundant in tropical regions. This study aimed to determine the diversity of breadfruit germplasm based on observed morphological characters including tree shape, leaves, flowers, and fruit. The research was conducted from August to October 2023, located on Yamdena Island, Tanimbar Islands Regency. This study used a qualitative method to determin local breadfruit germplasm diversity from information and target plants during the field observation. Data were obtained from key informants interviewed in two sub-districts in several villages, namely Lorulun, Amdasa, Arui Bab, Lorwembun and Kilmasa Villages, as well as target plants for observation in the village with high genetic diversity of germplasm, namely in Arui Bab Village. The data analysis used descriptive analysis to describe germplasm characteristics and cluster analysis with Dice Distance to describe similarities between germplasms. The results of this study showed that there was a diversity of local breadfruit germplasm on Yamdena Island, consisting of eight local varieties, namely Kulur Silai Mafut, Silai Mafut Kuning, Silai Melaus, Fen, Sif, Yombik, In and Kulur Watin. There are three groups of local varieties. Group I consists of six local varieties, namely Kulur Sif, Silai Melaus, Silai Mafut Kuning, Watin, Silai Mafut and In; Group II consists of one local variety, namely Kulur Fen; and Group III consists of one local variety, namely Kulur Yombik.